Coagglutination test for serotyping Pasteurella haemolytica. - Fodor, L (1996)
A coagglutination test was described for simple, fast, and reliable detection of Pasteurella haemolytica type-specific antigens in lung lesions even in the absence of viable P. haemolytica. The coagglutinating reagents were prepared by coating protein A-producing Staphylococcus aureus cells with hyperimmune sera raised against P. haemolytica type strains. Bacterial suspensions, saline extracts, and boiled saline extracts of the bacteria were used as antigens. Homologous reactions with all types of antigens were precise. Some cross-reactions were similar to those obtained by the indirect hemagglutination test, and some additional one-way cross-reactions were identified. The coagglutination test was used for serotyping 65 P. haemolytica field strains and for the detection of P. haemolytica type-specific antigens in the lung specimens of 62 calves and 78 sheep. Ninety-four percent of the field strains could be serotyped by the coagglutination test. P. haemolytica type-specific antigens were detected in the lung specimens of 3 calves and 5 sheep that had succumbed to naturally occurring P. haemolytica pneumonia and in the lungs of 20 calves experimentally infected with P. haemolytica A1. The coagglutination test detected type-specific antigens in 36% of the lung specimens of slaughtered field sheep but not in the lungs of slaughtered field cattle with small chronic lung lesions. No reaction occurred in the case of nonpneumonic calves and sheep or when pneumonic lesions were caused by other bacteria. No P. haemolytica strains could be isolated from lung samples that were coagglutination test negative. This test is recommended as an additional method for fast and reliable serotyping of P. haemolytica.